2019
DOI: 10.15869/itobiad.480114
|View full text |Cite
|
Sign up to set email alerts
|

Savunma Harcamaları ve Ekonomik Büyüme Üzerine Araştırma: ABD, Japonya ve Fransa Örneği

Abstract: Bu makale, en az iki hakem tarafından incelenmiş ve intihal içermediği teyit edilmiştir. / This article has been reviewed by at least two referees and confirmed to include no plagiarism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…33 In the research, a causality test was used in the frequency domain, and it was seen that there is a causal relationship between the defence expenditures and the economic growth in Turkey Yantur and Gurson (2019) analyzed the defence expenditures and per capita incomes of Japan, France, and the USA between 1960 and 2017 with a causality analysis. 34 In the study, it was observed that while the effect of the defence expenditures of the USA on national income per capita could not be determined, the defence expenditures of France and Japan had a positive effect on the national income per capita. Karakaya and Sahinoglu (2020) studied Turkey's data between 1984and 2016 with the help of the Johansen Cointegration Test and the ARDL Boundary Test.…”
Section: Empirical Studiesmentioning
confidence: 91%
“…33 In the research, a causality test was used in the frequency domain, and it was seen that there is a causal relationship between the defence expenditures and the economic growth in Turkey Yantur and Gurson (2019) analyzed the defence expenditures and per capita incomes of Japan, France, and the USA between 1960 and 2017 with a causality analysis. 34 In the study, it was observed that while the effect of the defence expenditures of the USA on national income per capita could not be determined, the defence expenditures of France and Japan had a positive effect on the national income per capita. Karakaya and Sahinoglu (2020) studied Turkey's data between 1984and 2016 with the help of the Johansen Cointegration Test and the ARDL Boundary Test.…”
Section: Empirical Studiesmentioning
confidence: 91%
“…Tüm bunlara ek olarak, savunma harcamaları hem iç hem de dış güvenliği geliştirerek ülkedeki yatırım ortamını iyileştirmekte ve dolayısıyla hem ulusal hem de uluslararası sermaye akışını hızlandırarak ekonomik büyümeyi olumlu şekilde etkileyebilmektedir. Bu görüşte savunma harcamalarının yayılma etkisi büyüme üzerinde pozitif bir sinerji katabilmektedir (Ataç, 2006, s. 8-9;Gökbunar ve Yanıkkaya, 2004, s. 161;Yantur ve Gürson, 2019). Arz yanlı Neo-klasik yaklaşımda ise, tam kamusal mal niteliği taşıyan savunma harcamalarında meydana gelebilecek bir artışın ekonomi üzerinde negatif dışsallık yaratabileceği ifade edilmektedir.…”
Section: Teorik çErçeveunclassified